Expanding Learning Spaces for Second Language Writers: A Writing Partners Project Across Program Boundaries - Zevgoli, Sophia; Dilaveri, Evi (Journal of Academic Writing, 2017)
Writing Partners projects have been instituted as ways of providing student writers with audiences other than their classmates and instructors. These projects may take various forms: e.g. high school students are paired with students at another school or with college students, etc. This article outlines a new approach to Writing Partners projects that utilized trained peer review and pairing of students from two successive academic programs related to writing: the English for Academic Purposes Program and the Writing Program. This project was piloted at Deree – The American College of Greece in Spring 2014. The aim of the project was to investigate whether this practice would have an impact on the participants’ writing abilities and attitudes towards writing. The findings of the project suggest that extending a community of writers “beyond classroom walls” (Gillis 1994: 64) and across academic program boundaries, and utilizing trained peer review, may enhance students’ writing skills and positively affect their attitude towards writing. This has been shown through qualitative and quantitative analysis of the students’ revised writing and an examination of their written reflections. The article proposes that similar Writing Partners projects be implemented at different institutions to enhance student writers’ skills.